Homework #5

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Solution

PROBLEM #2.21.
The wave function:
Ψ(𝑥, 0) = 𝐴𝑒 −𝑎|𝑥|
a. Normalizing the wave function, we can have:
(Note: since this function is even, we can achieve the following expression →
Much faster)
∞ ∞
2 2 −2𝑎𝑥
𝑒 −2𝑎𝑥 ∞
2
|𝐴|2
1 = ∫ |Ψ(𝑥, 0)| 𝑑𝑥 = 2|𝐴| ∫ 𝑒 𝑑𝑥 = 2|𝐴| | =
−2𝑎 0 𝑎
−∞ 0

⇒ 𝐴 = √𝑎
b. Find 𝜙(𝑘):
∞ ∞ 0
𝐴 𝐴
𝜙(𝑘) = ∫ 𝑒 −𝑎|𝑥| 𝑒 −𝑖𝑘𝑥 𝑑𝑥 = [∫ 𝑒 −𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥 + ∫ 𝑒 𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥]
√2𝜋 √2𝜋
−∞ 0 −∞

∞ 0 ∞ 0
𝐴 𝐴
= [∫ 𝑒 −𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥 + ∫ 𝑒 𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥] = [∫ 𝑒 −(𝑖𝑘+𝑎)𝑥 𝑑𝑥 + ∫ 𝑒 −(𝑖𝑘−𝑎)𝑥 𝑑𝑥]
√2𝜋 √2𝜋
0 −∞ 0 −∞

𝐴 𝑒 −(𝑖𝑘+𝑎)𝑥 ∞ 𝑒 −(𝑖𝑘−𝑎)𝑥 0 𝐴 1 1
= [(− ) | + (− )| ]= [(0 + ) + (− + 0)]
√2𝜋 𝑖𝑘 + 𝑎 0 𝑖𝑘 − 𝑎 −∞ √2𝜋 𝑖𝑘 + 𝑎 𝑖𝑘 − 𝑎
𝐴 −1 1 𝐴 −𝑖𝑘 − 𝑎 + 𝑖𝑘 − 𝑎
= ( + )=
√2𝜋 𝑖𝑘 − 𝑎 𝑖𝑘 + 𝑎 √2𝜋 −𝑘 2 − 𝑎2
𝑎 2𝑎
=√
2𝜋 𝑘 + 𝑎2
2

c. Construct Ψ(𝑥, 𝑡)
∞ 3 ∞
2 2
1 𝑎3 1 𝑖(𝑘𝑥−
ℏ𝑘
𝑡) 𝑎2 1 𝑖(𝑘𝑥−
ℏ𝑘
𝑡)
Ψ(𝑥, 𝑡 ) = 2√ ∫ 2 2
𝑒 2𝑚 𝑑𝑘 = ∫ 2 2
𝑒 2𝑚 𝑑𝑘
√2𝜋 2𝜋 𝑘 +𝑎 𝜋 𝑘 +𝑎
−∞ −∞

2
d. For large a, Ψ(𝑥, 0) is a sharp narrow spike whereas 𝜙(𝑘 ) ≅ √ is broad and flat;
𝜋𝑎
position is well- defined but momentum is ill-defined. For small a, Ψ(𝑥, 0) is a broad
3
√2𝑎
𝜋
and flat whereas 𝜙(𝑘 ) ≅ is a sharp narrow spike; position is ill-defined but
𝑘2
momentum is well-defined.
PROBLEM #2.22.
The wave function:
2
Ψ(𝑥, 0) = 𝐴𝑒 −𝑎𝑥

a. Normalizing the wave function, we have:



2 𝜋
1 = |𝐴|2 ∫ 𝑒 −2𝑎𝑥 𝑑𝑥 = |𝐴|2 √
2𝑎
−∞
1
2𝑎 4
𝐴=( )
𝜋
b. First let solve the following integral:
∞ ∞
𝑏2 1
−(𝑎𝑥 2 +𝑏𝑥) −𝑦 2 +( )
∫𝑒 𝑑𝑥 = ∫ 𝑒 4𝑎 𝑑𝑦
√𝑎
−∞ −∞

1 𝑏2 𝜋 𝑏2
−𝑦 2
= 𝑒 4𝑎 ∫𝑒 𝑑𝑦 = √ 𝑒 4𝑎
√𝑎 𝑎
−∞

As we take a look at the 𝜙(𝑘):



1 2
𝜙(𝑘) = 𝐴 ∫ 𝑒 −𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥
√2𝜋
−∞

We can easily see that:


∞ ∞
−(𝑎𝑥 2 +𝑏𝑥) 2
∫𝑒 𝑑𝑥 = ∫ 𝑒 −𝑎𝑥 𝑒 −𝑖𝑘𝑥 𝑑𝑥
−∞ −∞

With 𝑏 = 𝑖𝑘
∞ 1
−𝑎𝑥 2 −𝑖𝑘𝑥
2𝑎 4 𝜋 −𝑘 2
1
⇒ 𝜙(𝑘) = ∫ 𝑒 𝑒 𝑑𝑥 = ( ) √ 𝑒 4𝑎
√2𝜋 𝜋 𝑎
−∞

1 𝑘2
= 1 𝑒 −4𝑎
(2𝜋𝑎)4
Calculating Ψ(𝑥, 𝑡):

1 1 𝑘2 ℏ𝑡 2
𝑒 𝑖(𝑘𝑥−2𝑚𝑘
− )
Ψ(𝑥, 𝑡) = 1 ∫𝑒 4𝑎 𝑑𝑘
√2𝜋 (2𝜋𝑎)4
−∞

1 1 1 𝑖ℏ𝑡 2 −𝑖𝑥𝑘]
= 1 ∫ 𝑒 −[(4𝑎+2𝑚)𝑘 𝑑𝑘
√2𝜋 (2𝜋𝑎)4
−∞

By using the same equation:


∞ ∞
1 𝑖ℏ𝑡 2 −𝑖𝑥𝑘]
−(𝑎𝑥 2 +𝑏𝑥)
∫𝑒 𝑑𝑥 = ∫ 𝑒 −[(4𝑎+2𝑚)𝑘 𝑑𝑘
−∞ −∞

𝜋 𝑏2
= √ 𝑒 4𝑎
𝑎
𝑥2

1 √𝜋 1 𝑖ℏ𝑡
4( + )
⇒ Ψ(𝑥, 𝑡) = 1 𝑒 4𝑎 2𝑚
√2𝜋 (2𝜋𝑎)4 √ 1 + 𝑖ℏ𝑡
4𝑎 2𝑚
𝑎𝑥 2

1 2𝑖ℏ𝑎𝑡
1+
2𝑎 4 𝑒 𝑚
=( )
𝜋
√1 + 2𝑖ℏ𝑎𝑡
𝑚
c. Let
2ℏ𝑎𝑡
𝜃≡
𝑚
Then
𝑎𝑥 2 𝑎𝑥 2
2𝑎 𝑒 −1+𝑖𝜃 𝑒 −1−𝑖𝜃
|Ψ|2 = √
𝜋 √(1 + 𝑖𝜃)(1 − 𝑖𝜃)

From here, the exponent in the numerator could be calculated as:


𝑎𝑥 2 𝑎𝑥 2 (1 − 𝑖𝜃 + 1 + 𝑖𝜃) −2𝑎𝑥 2
− − = −𝑎𝑥 2 =
(1 + 𝑖𝜃) (1 − 𝑖𝜃) (1 + 𝑖𝜃)(1 − 𝑖𝜃) 1 + 𝜃2
2 2)
2𝑎 𝑒 −2𝑎𝑥 /(1+𝜃
⇒ |Ψ|2 =√
𝜋 √1 + 𝜃 2

Or, with we let


𝑎
𝜔≡√
1 + 𝜃2
The |Ψ|2 will be:

2 2 2
|Ψ|2 = √ 𝜔𝑒 −2𝜔 𝑥
𝜋

As t increases, the graph of |Ψ|2 flattens out and broadens.


d.
• Calculating 〈𝑥〉:

〈𝑥〉 = ∫ 𝑥 |Ψ|2 𝑑𝑥 = 0 (𝑜𝑑𝑑 𝑖𝑛𝑡𝑒𝑔𝑟𝑎𝑛𝑑)


−∞

• Calculating 〈𝑝〉:
𝑑 〈𝑥 〉
〈𝑝 〉 = 𝑚 =0
𝑑𝑡
• Calculating 〈𝑥 2 〉:


2 2 2 2 1 𝜋 1
〈𝑥 2 〉 = √ 𝜔 ∫ 𝑥 2 𝑒 −2𝜔 𝑥 𝑑𝑥 = √ 𝜔 √ =
𝜋 𝜋 4𝜔 2 2𝜔 2 4𝜔 2
−∞

• Calculating 〈𝑝2 〉:

𝑑2 Ψ
〈𝑝2 〉 = −ℏ2 ∫ Ψ ∗ 𝑑𝑥
𝑑𝑥 2
−∞
2
For simplicity, we will write Ψ = 𝐵𝑒 −𝑏𝑥
Where:
1
2𝑎 4 1
𝐵≡( )
𝜋 √1 + 𝑖𝜃
and
𝑎
𝑏≡
1 + 𝑖𝜃
𝑑2 Ψ 𝑑 2 2
⇒ 2
= 𝐵 (−2𝑏𝑥𝑒 −𝑏𝑥 ) = −2𝑏𝐵(1 − 2𝑏𝑥 2 )𝑒 −𝑏𝑥
𝑑𝑥 𝑑𝑥
𝑑2 Ψ ∗ 2
Ψ ∗
2
= −2𝑏|𝐵|2 (1 − 2𝑏𝑥 2 )𝑒 −(𝑏+𝑏 )𝑥
𝑑𝑥
In addition to that, we have:
o 𝑏 + 𝑏∗:
𝑎 𝑎 2𝑎
𝑏 + 𝑏∗ = + = 2
= 2𝜔2
1 + 𝑖𝜃 1 − 𝑖𝜃 1 + 𝜃
o |𝐵|2 :

2𝑎 1 2
|𝐵|2 = √ = √ 𝜔
𝜋 √1 + 𝜃 2 𝜋

Add them up, we have:


𝑑2 Ψ 2 2 2
Ψ 2
= −2𝑏 √ 𝜔(1 − 2𝑏𝑥 2 )𝑒 −2𝜔 𝑥
𝑑𝑥 𝜋

Put this expression to 〈𝑝2 〉, we have:



2 2 2
〈𝑝2 〉 = 2𝑏ℏ2 √ 𝜔 ∫ (1 − 2𝑏𝑥 2 )𝑒 −2𝜔 𝑥 𝑑𝑥
𝜋
−∞
2 𝜋 1 𝜋 𝑏
= 2𝑏ℏ2 √ 𝜔 (√ 2 − 2𝑏 2
√ 2 ) = 2𝑏ℏ2 (1 − )
𝜋 2𝜔 4𝜔 2𝜔 2𝜔 2

𝑏 𝑎 1 + 𝜃2 1 − 𝑖𝜃 1 + 𝑖𝜃 𝑎
1− = 1 − ( ) ( ) = 1 − = =
2𝜔 2 1 + 𝑖𝜃 2𝑎 2 2 2𝑏
𝑎
〈𝑝2 〉 = 2𝑏ℏ2 = ℏ2 𝑎
2𝑏
• Calculating 〈𝜎𝑥 〉:
1
𝜎𝑥 =
2𝜔
• Calculating 〈𝜎𝑝 〉:

𝜎𝑝 = ℏ√𝑎
e. Considering the uncertainty principle, we have:

1 ℏ ℏ 2ℏ𝑎𝑡 2 ℏ
𝜎𝑥 𝜎𝑝 = ℏ√𝑎 = √1 + 𝜃 =
2 √ 1+( ) ≥
2𝜔 2 2 𝑚 2

Close at 𝑡 = 0 at which time it is right at the uncertainty limit.

PROBLEM #2.23.
a.
1

∫(𝑥 3 − 3𝑥 2 + 2𝑥 − 1)𝛿(𝑥 + 2)𝑑𝑥


−3
When you get the integral consisted of delta function, the delta function will
produce zero everywhere, expect for the value that being set by the delta function.
1

⇒ ∫(𝑥 3 − 3𝑥 2 + 2𝑥 − 1)𝛿(𝑥 + 2)𝑑𝑥 = [(𝑥 3 − 3𝑥 2 + 2𝑥 − 1)] |


−2
−3
= (−2)3 − 3(−2)2 + 2(−2) − 1 = −25

b.

∫ [cos(3𝑥) + 2]𝛿(𝑥 − 𝜋)𝑑𝑥 = [cos(3𝑥) + 2] | = −1 + 2 = 1


𝜋
0
c. We can easily see that the value that determined by the delta function is outside
the value of the bound given by the integral. Therefore, we have:
+1

∫ 𝑒 |𝑥|+3 . 𝛿(𝑥 − 2)𝑑𝑥 = 0


−1

PROBLEM #2.24.
a. Let 𝑦 ≡ 𝑐𝑥,
So
1 𝐼𝑓 𝑐 > 0, 𝑦: −∞ → ∞
𝑑𝑥 = 𝑑𝑦 {
𝑐 𝐼𝑓 𝑐 < 0, 𝑦: ∞ → −∞

1 𝑦 1
∞ ∫ 𝑓 ( ) 𝛿(𝑦)𝑑𝑦 = 𝑓(0) (𝑐 > 0)
𝑐 𝑐 𝑐
−∞
∫ 𝑓(𝑥) 𝛿(𝑐𝑥)𝑑𝑥 = −∞ ∞
−∞ 1 𝑦 1 1 1
∫ 𝑓 ( ) 𝛿(𝑦)𝑑𝑦 = − ∫ 𝑓(𝑥) 𝛿(𝑥)𝑑𝑥 = − 𝑓(0)
𝑐 𝑐 𝑐 |𝑐| 𝑐
{ ∞ −∞

In either case
∞ ∞
1 1
∫ 𝑓(𝑥)𝛿(𝑐𝑥) 𝑑𝑥 = 𝑓(0) = ∫ 𝑓(𝑥) 𝛿(𝑥) 𝑑𝑥
|𝑐| |𝑐|
−∞ −∞

1
𝛿(𝑐𝑥) = 𝛿(𝑥)
|𝑐|
b.
∞ ∞
𝑑𝜃 ∞ 𝑑𝑓
∫ 𝑓(𝑥) 𝑑𝑥 = 𝑓𝜃 | − ∫ 𝜃𝑑𝑥
𝑑𝑥 −∞ 𝑑𝑥
−∞ −∞

1, 𝑥 > 0
Since 𝜃(𝑥) = {
0, 𝑥 < 0
∞ ∞ 0
𝑑𝜃 𝑑𝑓 𝑑𝑓
⇒ ∫ 𝑓(𝑥) 𝑑𝑥 = 𝑓(∞) − 0. 𝑓(−∞) − ∫ 𝑑𝑥 − ∫ . 0𝑑𝑥
𝑑𝑥 𝑑𝑥 𝑑𝑥
−∞ 0 −∞

𝑑𝑓
= 𝑓(∞) − ∫ 𝑑𝑥 = 𝑓(∞) − 𝑓(∞) + 𝑓(0)
𝑑𝑥
0

= 𝑓(0) = ∫ 𝑓(𝑥)𝛿(𝑥)𝑑𝑥
−∞

So
𝑑𝜃
= 𝛿(𝑥)
𝑑𝑥
Note: The 𝜃 function is constant (so derivative is 0) except at 𝑥 = 0, where the
derivative infinite.

You might also like